Complete Blood Count Parameters in Arthritis - KC, Shiva Raj; Shrestha, S; KC, G; Gyawali, P; Dahal, S; Maharjan, B (Nepal Medical College Journal, 2020)
Osteoarthritis, rheumatoid arthritis, and gout are frequently encountered diseases in the orthopedic clinic. CRP is done to evaluate and monitor these disease processes. This study aimed to evaluate total leukocyte count with differential count, neutrophil/lymphocyte ratio, platelet, platelet/lymphocyte ratio, mean platelet volume (MPV), platelet distribution width (PDW), and plateletcrit in patients with arthritis. This was a cross-sectional study conducted at KIST Medical College, Teaching Hospital from 15 Ashad 2075 to 14 Ashad 2076. The patient’s demographic data and laboratory findings: total leukocyte count, differential count, hemoglobin, platelet count, plateletcrit, mean platelet volume, platelet distribution width, and plateletcrit. CRP, ESR, RA factor/anti-CCP, and Uric acid tests were also performed. Among 67 patients, osteoarthritis was seen in 53 (79.1%), rheumatoid arthritis among 11(16.4%), and Gout among 3(4.5%). The ROC area under the curve was within acceptable limits for the neutrophil count, neutrophil/lymphocyte ratio, mean platelet volume, platelet distribution width. The sensitivity and specificity of the neutrophil count were 75% and 62% respectively (cut-off: 64.5%). Neutrophil/Lymphocyte ratio was increased and correlated with CRP (p-value: <0.001). PDW had a sensitivity of 90% and specificity of 83.0% (cut-off: 16.8 CV). For MPV, the sensitivity was 80% and specificity was 81% (cut-off: 9.1 fL). At 1.92 cut-off value, the sensitivity and specificity of neutrophil/lymphocyte ratio were 80.0% and 62.0% respectively. CBC parameters can provide an important clue to the treating physician, which helps to manage a patient with arthritis effectively. Neutrophil count, Neutrophil/Lymphocyte ratio, MPV, and PDW correlated with other inflammatory biomarkers and can be used to assess the patient with arthritis.